Nitrogen-doped porous carbon materials, powders and methods of making and uses thereof

CN122918607APending Publication Date: 2026-10-16LANGFANG NORMAL UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611345044.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-01
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,CN121669170A所述方案仍存在以下不足:其采用阳极氧化方式仅能实现OH⁻的物理积聚,无法调控碳材料的本征电子结构;其使用无掺杂的活性碳布,缺乏与OH⁻协同的本征活性位点;且未提出材料与器件一体化的工程化方案

Benefits of technology

[0020] The preparation method of this invention can improve the adsorption capacity and selectivity of nitrogen-doped porous carbon materials for CO2. Furthermore, this preparation method can reduce the regeneration energy consumption of nitrogen-doped porous carbon materials. Even further, this preparation method can improve the adsorption capacity of nitrogen-doped porous carbon materials at high flow rates. Still further, this preparation method can improve the long-term stability of nitrogen-doped porous carbon materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122918607A_ABST
    Figure CN122918607A_ABST
Patent Text Reader

Abstract

The application discloses a kind of nitrogen-doped porous carbon materials, powder and its preparation method and use.The preparation method of the nitrogen-doped porous carbon material includes the following steps: (1) the nickel foam is immersed in the precursor solution including carbon source and nitrogen source to carry out hydrothermal reaction, and the loaded nickel foam is obtained;The NPCS is obtained by carbonizing the loaded nickel foam @NF;(2) with NPCS @NF as working electrode, electrochemical treatment is carried out in three-electrode system, and nitrogen-doped porous carbon material is obtained;Wherein, working electrode is cathode, and electrolyte is nitrate aqueous solution.The preparation method can improve the adsorption capacity and selectivity of nitrogen-doped porous carbon material to CO2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a nitrogen-doped porous carbon material, powder, preparation method thereof, and applications. Background Technology

[0002] Currently, amine solutions are commonly used to absorb carbon dioxide from flue gas in coal-fired power plants. However, this method suffers from high operating costs, high regeneration energy consumption, and drawbacks such as equipment corrosion and amine degradation. Solid-state adsorption methods, represented by porous carbon materials, offer advantages such as simple operation, no corrosion, and low energy consumption, and are considered the direction for next-generation carbon capture technology. Porous carbon materials possess high specific surface area, tunable pore structure, and excellent physicochemical stability. However, unmodified porous carbon materials mainly rely on physical adsorption, and their adsorption capacity and selectivity are insufficient to meet industrial separation requirements under low CO2 partial pressures. Existing technologies typically introduce heteroatoms such as nitrogen and sulfur to construct Lewis basic sites; or introduce amines or metal oxides to provide chemisorption sites. The improvement effect of these methods is limited; furthermore, the introduction of amines or metal oxides generates thermodynamically stable bulk carbonates, resulting in high regeneration temperatures and easy loss of active components.

[0003] CN116375026A discloses a method for preparing nitrogen-doped hollow carbon nanospheres. The method involves mixing glucose, sodium oleate, block polymer P123, and water, followed by hydrothermal carbonization to obtain a carbon nanosphere precursor. The precursor, urea, an activator, and water are then mixed, dried, and calcined under a protective atmosphere to obtain nitrogen-doped hollow carbon nanospheres. The nitrogen-doped hollow carbon nanospheres obtained by this method exhibit low selectivity for carbon dioxide and low adsorption capacity.

[0004] CN117619349A discloses a method for preparing amine-modified nitrogen-doped carbon materials. The method involves mixing and grinding a sugar-based carbon source and a nitrogen-containing amine carbon source, then carbonizing the resulting mixture to obtain a porous carbon material. The porous carbon material is then impregnated in an amine compound to obtain the amine-modified nitrogen-doped carbon material. This preparation method uses amines to modify the nitrogen-doped carbon material, resulting in a low adsorption capacity for carbon dioxide.

[0005] CN121669170A discloses a method for preparing a charged adsorbent for direct air capture. The method involves first activating activated carbon cloth to obtain a porous carbon cloth; then charging the porous carbon cloth in a three-electrode system of caustic soda solution to obtain a precursor for the charged adsorbent; wherein the porous carbon cloth serves as the working electrode connected to the positive terminal of a power supply, and the counter electrode is connected to the negative terminal; finally, the precursor is subjected to a second activation treatment to obtain the charged adsorbent. This charged adsorbent exhibits low selectivity for carbon dioxide and a low adsorption capacity. However, the method described in CN121669170A still has the following shortcomings: its anodic oxidation method only achieves the physical accumulation of OH⁻, failing to control the intrinsic electronic structure of the carbon material; it uses undoped activated carbon cloth, lacking intrinsic active sites that cooperate with OH⁻; and it does not propose an engineering solution integrating materials and devices. Compared with the present invention, the present invention has at least the following differences: (1) it uses cathodic reduction instead of anodic oxidation; (2) it uses nitrogen-doped porous carbon spheres instead of undoped activated carbon cloth; (3) it achieves synergy between nitrogen species reconstruction and in-situ OH⁻ generation; and (4) it provides an integral device form. Summary of the Invention

[0006] In view of this, one object of the present invention is to provide a method for preparing nitrogen-doped porous carbon materials, which can improve the adsorption capacity and selectivity of nitrogen-doped porous carbon materials for CO2. Furthermore, the preparation method can reduce the regeneration energy consumption of nitrogen-doped porous carbon materials. Even further, the preparation method can improve the adsorption capacity of nitrogen-doped porous carbon materials at high flow rates. Still further, the preparation method can improve the long-term stability of nitrogen-doped porous carbon materials.

[0007] Another object of the present invention is to provide a method for preparing nitrogen-doped porous carbon powder, which can improve the adsorption capacity and selectivity of nitrogen-doped porous carbon powder for CO2. Furthermore, this preparation method can reduce the regeneration energy consumption of nitrogen-doped porous carbon powder. Even further, this preparation method can improve the long-term stability of nitrogen-doped porous carbon powder.

[0008] Another object of the present invention is to provide a nitrogen-doped porous carbon material. Yet another object of the present invention is to provide a nitrogen-doped porous carbon powder. A further object of the present invention is to provide a use for the above-mentioned nitrogen-doped porous carbon material or nitrogen-doped porous carbon powder.

[0009] The above-mentioned technical objectives are achieved through the following technical solutions.

[0010] On one hand, the present invention provides a method for preparing nitrogen-doped porous carbon materials, comprising the following steps: (1) The nickel foam was immersed in a precursor solution containing carbon and nitrogen sources for hydrothermal reaction to obtain supported nickel foam; the supported nickel foam was carbonized to obtain NPCS@NF; (2) Using NPCS@NF as the working electrode, electrochemical treatment was carried out in a three-electrode system to obtain nitrogen-doped porous carbon material; wherein, the working electrode is the cathode and the electrolyte is an aqueous solution of nitrate.

[0011] According to the preparation method of the present invention, preferably, in step (2), the counter electrode is platinum and the reference electrode is Ag / AgCl; a negative potential of -0.5 to -2.5V is applied to the working electrode.

[0012] According to the preparation method of the present invention, preferably, in step (1), the carbon source is selected from one or more of glucose, sucrose, and cellulose, and the nitrogen source is selected from one or more of urea, ethylenediamine, triethylamine, and acrylamide; the mass ratio of carbon source to nitrogen source is (3-6):(1-3); In step (2), the nitrate in the nitrate aqueous solution is selected from one or more of potassium nitrate, sodium nitrate, and lithium nitrate, and the concentration of the nitrate aqueous solution is 0.1 to 0.9 mol / L.

[0013] According to the preparation method of the present invention, preferably, the precursor solution further includes a zinc carboxylate salt, wherein the zinc carboxylate salt is selected from one or more of zinc formate, zinc acetate, and zinc propionate, and the mass ratio of the carbon source to the zinc carboxylate salt is (3-6):(0.05-0.5).

[0014] According to the preparation method of the present invention, preferably, the precursor solution further includes water and an aliphatic alcohol having 1 to 6 carbon atoms, wherein the volume ratio of water to aliphatic alcohol is 85:(5 to 25).

[0015] According to the preparation method of the present invention, preferably, the hydrothermal reaction is carried out at a temperature of 390-450K for a time of 5-10 hours; Carbonization is carried out under a nitrogen atmosphere at a temperature of 650–850 K for a time of 0.5–3 h.

[0016] On the other hand, the present invention provides a method for preparing nitrogen-doped porous carbon powder, comprising the following steps: (1) The nickel foam was immersed in a precursor solution containing carbon and nitrogen sources for hydrothermal reaction to obtain supported nickel foam; the supported nickel foam was carbonized to obtain NPCS@NF; (2) Using NPCS@NF as the working electrode, electrochemical treatment was carried out in a three-electrode system to obtain nitrogen-doped porous carbon material; wherein, the working electrode is the cathode and the electrolyte is an aqueous nitrate solution; (3) Separate the powder attached to the surface of the nitrogen-doped porous carbon material from the matrix nickel foam to obtain nitrogen-doped porous carbon powder.

[0017] In another aspect, the present invention provides a nitrogen-doped porous carbon material, which is obtained by the above-described preparation method.

[0018] In another aspect, the present invention provides a nitrogen-doped porous carbon powder, which is obtained by the above-described preparation method.

[0019] In another aspect, the present invention provides the use of the above-mentioned nitrogen-doped porous carbon material or nitrogen-doped porous carbon powder in the adsorption of CO2 gas.

[0020] The preparation method of this invention can improve the adsorption capacity and selectivity of nitrogen-doped porous carbon materials for CO2. Furthermore, this preparation method can reduce the regeneration energy consumption of nitrogen-doped porous carbon materials. Even further, this preparation method can improve the adsorption capacity of nitrogen-doped porous carbon materials at high flow rates. Still further, this preparation method can improve the long-term stability of nitrogen-doped porous carbon materials. Attached Figure Description

[0021] Figure 1 The graph shows the adsorption capacity of the nitrogen-doped porous carbon material of Example 1 and the nitrogen-doped porous carbon powder of Example 2 at different gas flow rates.

[0022] Figure 2 The image shows the DSC curve of the nitrogen-doped porous carbon material in Example 1. Detailed Implementation

[0023] Preparation method of nitrogen-doped porous carbon materials The method for preparing nitrogen-doped porous carbon material of the present invention includes the following steps: (1) preparing NPCS@NF; (2) electrochemical treatment. In the nitrogen-doped porous carbon material obtained by this preparation method, the nitrogen-doped porous carbon material is attached to the nickel foam matrix. The steps are described in detail below.

[0024] Steps for preparing NPCS@NF Nickel foam is immersed in a precursor solution containing carbon and nitrogen sources for hydrothermal reaction to obtain supported nickel foam; the supported nickel foam is then carbonized to obtain NPCS@NF. Preferably, the nickel foam can be immersed in the precursor solution. In this step, the generated nitrogen-doped porous carbon material grows in situ and anchors to the surface of the nickel foam.

[0025] The porosity of nickel foam can be ≥90%; preferably, the porosity of nickel foam is ≥95%.

[0026] The preferred form of nickel foam is pretreated nickel foam. Pretreatment of nickel foam can be performed as follows: the raw material is cleaned with an organic solvent, then soaked in an aqueous solution of an inorganic acid to obtain cleaned nickel foam. The cleaned nickel foam is then washed until neutral and dried to obtain pretreated nickel foam.

[0027] The organic solvent can be selected from one or more of acetone, methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate, butyl acetate, and tetrahydrofuran. According to one embodiment of the present invention, the organic solvent is acetone. The nickel foam raw material can be cleaned using ultrasonic methods. The cleaning time can be 10–50 min; preferably 20–40 min.

[0028] The inorganic acid aqueous solution can be selected from one or more of HCl aqueous solution and H2SO4 aqueous solution. The concentration of the inorganic acid aqueous solution can be 0.5-3 mol / L; preferably 1-2 mol / L. The soaking time can be 5-30 min; preferably 10-20 min.

[0029] The cleaned nickel foam can be washed with water. The drying temperature can be 300-360K; preferably 320-350K; more preferably 330-340K.

[0030] The carbon source may be selected from one or more of glucose, sucrose, and cellulose; preferably, the carbon source is glucose. The nitrogen source is selected from one or more of urea, ethylenediamine, triethylamine, and acrylamide; preferably, the nitrogen source is urea. The mass ratio of the carbon source to the nitrogen source is (3-6):(1-3); preferably (4-5.5):(1.5-2.5); more preferably (4.5-5):(2-2.5).

[0031] The precursor solution may also include a zinc carboxylate salt. The zinc carboxylate salt is selected from one or more of zinc formate, zinc acetate, and zinc propionate; preferably, the zinc carboxylate salt is zinc acetate. The mass ratio of carbon source to zinc carboxylate salt is (3-6):(0.05-0.5); preferably (3.5-5):(0.1-0.4); more preferably (4-4.5):(0.2-0.3).

[0032] The precursor solution may also include a solvent. The solvent includes water and an aliphatic alcohol having 1 to 6 carbon atoms. Preferably, the solvent includes water and an aliphatic alcohol having 1 to 3 carbon atoms. Preferably, the aliphatic alcohol is an aliphatic monohydric alcohol. Examples of aliphatic alcohols include, but are not limited to, methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, sec-butanol, and tert-butanol. The volume ratio of water to the aliphatic alcohol can be 85:(5 to 25); preferably 85:(10 to 20).

[0033] Based on 100 mL of solvent, the carbon source content is 3–6 g; preferably 4–5.5 g; more preferably 4–4.5 g.

[0034] In some embodiments, the process further includes preparing a precursor solution. The raw materials are mixed and then sonicated at 288–308 K; preferably 293–303 K, to obtain the precursor solution. Magnetic stirring may be used during the sonication process.

[0035] The hydrothermal reaction can be carried out at a temperature of 390–450 K; preferably, the hydrothermal reaction is carried out at a temperature of 410–440 K; more preferably, the hydrothermal reaction is carried out at a temperature of 420–430 K.

[0036] The hydrothermal reaction time can be 5 to 10 hours; preferably 6 to 9 hours; more preferably 7 to 8 hours.

[0037] The hydrothermal reaction can be carried out in an autoclave. The angle between the nickel foam and the bottom surface of the autoclave can be 30–60°; preferably 40–50°.

[0038] In some embodiments, the following steps are also included: after the hydrothermal reaction is completed, the mixture is naturally cooled to 288–308 K; preferably 293–303 K, to obtain the reaction product. The reaction product is then washed and dried to obtain supported nickel foam.

[0039] The reaction product can be washed with water or a C1-C3 aliphatic monohydric alcohol. Specifically, it can be washed first with water, and then washed with an aliphatic monohydric alcohol. The number of water washes can be 1 to 5 times; preferably 2 to 4 times. The number of aliphatic monohydric alcohol washes can be 1 to 4 times; preferably 2 to 3 times. Examples of aliphatic monohydric alcohols include, but are not limited to, methanol, ethanol, n-propanol, and isopropanol. According to one embodiment of the present invention, the aliphatic monohydric alcohol is ethanol.

[0040] The drying temperature can be 300–360 K; preferably 320–350 K; more preferably 330–340 K. The drying time can be 7–20 h; preferably 10–18 h; more preferably 12–15 h.

[0041] The carbonization temperature is 650–850 K; preferably 700–800 K; more preferably 750–790 K. The carbonization time is 0.5–3 h; preferably 1–2 h; more preferably 1–1.5 h. The heating rate from the initial temperature to the carbonization temperature can be 3–18 K / min; preferably 5–15 K / min; more preferably 8–12 K / min.

[0042] Carbonization can be carried out in an inert gas atmosphere. The inert gas can be selected from one or more of nitrogen, argon, helium, and neon. Preferably, the inert gas is nitrogen.

[0043] Carbonization can be carried out in a tube furnace. An inert gas is introduced into the tube furnace to create an inert gas atmosphere. The flow rate of the inert gas can be 50–200 mL / min; preferably 80–150 mL / min; more preferably 100–120 mL / min.

[0044] The carbon compound obtained by carbonization can be naturally cooled to 288–308 K, preferably 293–303 K, under the protection of an inert gas, to obtain NPCS@NF. The inert gas can be selected from one or more of nitrogen, argon, helium, and neon. Preferably, the inert gas is nitrogen.

[0045] Steps of electrochemical treatment Nitrogen-doped porous carbon materials were obtained by electrochemical treatment using NPCS@NF as the working electrode in a three-electrode system. In the three-electrode system of this invention, the working electrode is the cathode.

[0046] The counter electrode is platinum. The platinum can be platinum wire or platinum mesh. According to one embodiment of the invention, the counter electrode is platinum wire. The diameter of the platinum wire can be 0.1–1 mm; preferably 0.3–0.8 mm; more preferably 0.5–0.6 mm. The length of the platinum wire can be 5–15 cm; preferably 8–12 cm; more preferably 10–11 cm.

[0047] The length of the working electrode can be 1–8 cm; preferably 3–7 cm; more preferably 5–6 cm. The width can be 0.5–5 cm; preferably 1–4 cm; more preferably 2–3 cm. The thickness is 0.2–3 mm; preferably 0.5–2 mm; more preferably 1–1.5 mm.

[0048] The counter electrode is an Ag / AgCl electrode. Specifically, the counter electrode is an Ag / AgCl electrode internally filled with a saturated KCl solution.

[0049] The electrolyte is an aqueous solution of nitrates. The nitrate in the aqueous solution is selected from one or more of potassium nitrate, sodium nitrate, and lithium nitrate; preferably, it is selected from one or more of potassium nitrate and sodium nitrate; more preferably, it is potassium nitrate.

[0050] The concentration of the nitrate aqueous solution can be 0.1–0.9 mol / L; preferably 0.3–0.8 mol / L; more preferably 0.5–0.6 mol / L.

[0051] A negative potential of -0.5 to -2.5V is applied to the working electrode; preferably, a negative potential of -0.8 to -2.0V is applied to the working electrode; more preferably, a negative potential of -1.0 to -1.2V is applied to the working electrode. This potential is relative to the potential of a standard hydrogen electrode.

[0052] The application time can be 20 to 70 minutes; preferably 30 to 60 minutes; more preferably 40 to 50 minutes.

[0053] During the application of voltage to the working electrode, the electrolyte can be continuously stirred using magnetic stirring. The stirring speed can be 50–300 rpm; preferably 80–200 rpm; more preferably 100–150 rpm.

[0054] The electrochemically treated NPCS@NF can be rinsed with water and then vacuum dried to obtain nitrogen-doped porous carbon material. The drying temperature can be 310–370 K; preferably 330–360 K; more preferably 340–350 K. The drying time can be 7–18 h; preferably 10–15 h; more preferably 12–13 h.

[0055] Preparation method of nitrogen-doped porous carbon powder The method for preparing nitrogen-doped porous carbon powder of the present invention includes the following steps: (1) preparing NPCS@NF; (2) electrochemical treatment; and (3) separation. Steps (1) and (2) are as described above and will not be repeated here. Step (3) will be described in detail below.

[0056] The powder adhering to the surface of the nitrogen-doped porous carbon material is separated from the nickel foam matrix to obtain nitrogen-doped porous carbon powder. Specifically, the nitrogen-doped porous carbon material can be ultrasonically treated in an aliphatic monohydric alcohol containing C1-C3 to obtain detached powder; the detached powder is then dried to obtain nitrogen-doped porous carbon powder.

[0057] Examples of aliphatic monohydric alcohols containing C1-C3 include, but are not limited to, methanol, ethanol, propanol, and isopropanol. According to one embodiment of the invention, the aliphatic monohydric alcohol is ethanol.

[0058] The ultrasonic treatment time can be 15-60s; preferably 20-50s; more preferably 30-40s.

[0059] The ultrasonic frequency can be 20–80 kHz; preferably 30–70 kHz; more preferably 40–50 kHz.

[0060] The drying temperature can be 300–360 K; preferably 320–350 K; more preferably 330–340 K. The drying time can be 0.5–5 h; preferably 1–4 h; more preferably 2–3 h.

[0061] Nitrogen-doped porous carbon materials, nitrogen-doped porous carbon powder and their applications The nitrogen-doped porous carbon material of the present invention is prepared by the above-described method. The nitrogen-doped porous carbon powder of the present invention is prepared by the above-described method. The nitrogen-doped porous carbon material and nitrogen-doped porous carbon powder of the present invention exhibit high adsorption capacity and selectivity for CO2. Therefore, the present invention provides the use of the above-described nitrogen-doped porous carbon material or nitrogen-doped porous carbon powder in the adsorption of CO2 gas.

[0062] CO2 gas can exist in a gas mixture with other gases, such as a mixture of CO2 and N2. The volume percentage of CO2 in the gas mixture can be 10–25 vol%, preferably 15–20 vol%.

[0063] Specifically, the gas is brought into contact with nitrogen-doped porous carbon material or nitrogen-doped porous carbon powder. The gas can be CO2 gas or a mixture of gases containing CO2.

[0064] The gas flow rate can be 20–80 mL / min. -1 The preferred concentration is 30–70 mL / min. -1 More preferably, 40–60 mL·min -1 .

[0065] The gas can be in contact with nitrogen-doped porous carbon material or nitrogen-doped porous carbon powder at a temperature of 290–340 K; preferably 300–330 K; more preferably 310–320 K.

[0066] Example 1 (1) Dissolve 4.5g glucose, 2.0g urea and 0.2g zinc acetate in a solvent consisting of 85mL deionized water and 15mL ethanol, and then sonicate at 298K for 30min. During the sonication process, magnetic stirring is used to obtain the precursor solution.

[0067] The nickel foam raw material was ultrasonically cleaned with acetone for 30 min, and then soaked in a 1 mol / L HCl aqueous solution for 15 min to obtain cleaned nickel foam. The cleaned nickel foam was washed with deionized water until neutral, and then dried at 333 K to obtain pretreated nickel foam (5 cm long, 2 cm wide, 1.5 mm thick, with a porosity ≥95%).

[0068] Pretreated nickel foam and the precursor solution were placed in a PTFE-lined stainless steel autoclave; the angle between the pretreated nickel foam and the bottom of the autoclave was 45°, and the pretreated nickel foam was completely immersed in the precursor solution. The autoclave was sealed and hydrothermally reacted at 423 K for 8 hours, then naturally cooled to 298 K to obtain the reaction product. The reaction product was washed three times with deionized water and twice with ethanol, and then dried at 333 K for 12 hours to obtain loaded nickel foam.

[0069] The supported nickel foam was placed in a tube furnace, and nitrogen gas (99.999% purity) was introduced into the furnace to create a nitrogen atmosphere. The supported nickel foam was then carbonized at 773 K for 1 hour to obtain a carbide. The nitrogen flow rate was 100 mL / min, and the heating rate from the initial temperature to 773 K was 10 K / min. The carbide was then naturally cooled to 298 K under nitrogen atmosphere protection to obtain NPCS@NF.

[0070] (2) Using NPCS@NF as the working electrode, a platinum wire (0.5 mm in diameter and 10 cm in length) as the counter electrode, an Ag / AgCl electrode filled with KCl solution as the reference electrode, and a 0.5 mol / L KNO3 aqueous solution as the electrolyte. Using an electrochemical workstation (BioLogic SP-150), a constant negative potential of -1.0 V (relative to the standard hydrogen electrode, vs. SHE) was applied to the working electrode by chronoamperometry for 40 min to obtain electrochemically treated NPCS@NF. During the application of voltage to the working electrode, the electrolyte was continuously stirred using magnetic stirring at a speed of 100 rpm. The electrochemically treated NPCS@NF was rinsed with 500 mL of deionized water and then vacuum dried at 348 K for 12 h to obtain nitrogen-doped porous carbon material.

[0071] Example 2 Nitrogen-doped porous carbon material was prepared according to the method in Example 1. The nitrogen-doped porous carbon material was ultrasonically treated in ethanol for 30 s to obtain detached powder; wherein the ultrasonic frequency was 40 kHz. The detached powder was dried at 333 K for 2 h to obtain nitrogen-doped porous carbon powder.

[0072] Example 3 Except for step (2), in which a constant negative potential of -0.8V (relative to the standard hydrogen electrode, vs. SHE) is applied to the working electrode, the rest is the same as in Example 2.

[0073] Example 4 Except for step (2), in which a constant negative potential of -1.5V (relative to the standard hydrogen electrode, vs. SHE) is applied to the working electrode, the rest is the same as in Example 2.

[0074] Example 5 Except for step (2), where the electrolyte is a 0.5 mol / L NaNO3 aqueous solution, the rest is the same as in Example 2.

[0075] Comparative Example 1 4.5 g of glucose was dissolved in a solvent consisting of 85 mL of deionized water and 15 mL of ethanol, and then sonicated at 298 K for 30 min with magnetic stirring during the sonication process to obtain a precursor solution.

[0076] The nickel foam raw material was ultrasonically cleaned with acetone for 30 min, and then soaked in a 1 mol / L HCl aqueous solution for 15 min to obtain cleaned nickel foam. The cleaned nickel foam was washed with deionized water until neutral, and then dried at 333 K to obtain pretreated nickel foam (5 cm long, 2 cm wide, 1.5 mm thick, with a porosity ≥95%).

[0077] Pretreated nickel foam and the precursor solution were placed in a PTFE-lined stainless steel autoclave; the angle between the pretreated nickel foam and the bottom of the autoclave was 45°, and the pretreated nickel foam was completely immersed in the precursor solution. The autoclave was sealed and hydrothermally reacted at 423 K for 8 hours, then naturally cooled to 298 K to obtain the reaction product. The reaction product was washed three times with deionized water and twice with ethanol, and then dried at 333 K for 12 hours to obtain loaded nickel foam.

[0078] The supported nickel foam was placed in a tube furnace, and nitrogen gas (99.999% purity) was introduced into the furnace to create a nitrogen atmosphere. The supported nickel foam was then carbonized at 773 K for 1 hour to obtain a carbide. The nitrogen flow rate was 100 mL / min, and the heating rate from the initial temperature to 773 K was 10 K / min. The carbide was then naturally cooled to 298 K under nitrogen atmosphere protection to obtain CS@NF.

[0079] CS@NF was ultrasonically treated in ethanol for 30 seconds to obtain detached powder; the ultrasonic frequency was 40 kHz. The detached powder was dried at 333 K for 2 hours to obtain CS powder (carbon material).

[0080] Comparative Example 2 NPCS@NF was prepared according to the method in Example 1. NPCS@NF was ultrasonically treated in ethanol for 30 s to obtain detached powder; wherein the ultrasonic frequency was 40 kHz. The detached powder was dried at 333 K for 2 h to obtain NPCS powder (carbon material).

[0081] Comparative Example 3 (1) NPCS@NF was prepared according to the method of Example 1.

[0082] (2) Using NPCS@NF as the anode working electrode, a platinum wire (0.5 mm in diameter and 10 cm in length) as the counter electrode, an Ag / AgCl electrode filled with KCl solution as the reference electrode, and a 6 mol / L KOH aqueous solution as the electrolyte. A constant positive potential of +0.565 V (relative to the standard hydrogen electrode, vs. SHE) was applied to the working electrode using a chronoamperometry method for 40 min to obtain electrochemically treated NPCS@NF. During the voltage application to the working electrode, the electrolyte was continuously stirred using a magnetic stirrer at a speed of 100 rpm. The electrochemically treated NPCS@NF was rinsed with 500 mL of deionized water and then vacuum dried at 348 K for 12 h to obtain A-NPCS (carbon material).

[0083] Comparative Example 4 100 mg of NPCS powder obtained according to the method of Comparative Example 2 was immersed in 50 mL of 6 mol / L KOH aqueous solution. Then, the KOH aqueous solution containing NPCS powder was magnetically stirred at 298 K for 40 min to obtain impregnated NPCS powder. The impregnated NPCS powder was rinsed with 500 mL of deionized water and then vacuum dried at 348 K for 12 h to obtain NPCS-KOH (carbon material).

[0084] Experimental Example 1 The nitrogen-doped porous carbon materials, powders, or carbon materials obtained in the examples and comparative examples were tested as follows, and the results are shown in Table 1: CO2 adsorption capacity (static): Tested using a high-precision gas adsorption analyzer (BSD-PM2, Best Instruments Technology (Beijing) Co., Ltd.). Before testing, the sample was degassed under vacuum at 393 K for 6 h to completely remove adsorbed moisture and gas from the pores. Adsorption isotherms were recorded at 313 K within the pressure range of 0-1.0 bar.

[0085] CO2 adsorption capacity (dynamic) and CO2 / N2 selectivity (experimental values): The sample was packed into a stainless steel adsorption column with an inner diameter of 8 mm and a length of 150 mm, and both ends of the column were fixed with quartz wool. Before the test, the adsorption column was purged at 393 K with a flow rate of 30 mL / min. -1 The simulated flue gas was degassed in situ with high-purity N2 for 6 h, then cooled to 313 K. The simulated flue gas consisted of CO2 and N2 in a volume ratio of 15:85. The simulated flue gas was then purged at a rate of 50 mL / min. -1 The CO2 concentration in the adsorption column is fed at a flow rate of [value missing]. The CO2 concentration at the adsorption column outlet is monitored in real time by an online CO2 analyzer (Siemens ULTRAMAT 23), with a data acquisition frequency of 1 second. Bed breakthrough is considered to occur when the CO2 concentration at the adsorption column outlet reaches 95% of the feed concentration. The dynamic CO2 adsorption capacity is calculated by integrating the breakthrough curve. The CO2 / N2 selectivity (experimental value) is derived from the adsorption capacity ratio based on material balance.

[0086]

[0087] Comparing Examples 1-4 with Comparative Examples 1-2, it can be seen that nitrogen doping and electrochemical processes can significantly improve the adsorption capacity and selectivity of porous carbon materials for CO2.

[0088] As shown in Table 1, the dynamic CO2 adsorption capacity and CO2 / N2 selectivity of the nitrogen-doped porous carbon material (monolithic device) in Example 1 are better than those of the nitrogen-doped porous carbon powder in Example 2.

[0089] Comparing Examples 1-4 with Comparative Example 3, it can be seen that cathodic reduction treatment can better improve the adsorption capacity and selectivity of nitrogen-doped porous carbon materials for CO2 compared with anodic oxidation treatment. This may be because the anodic oxidation environment cannot reconstruct the chemical form of nitrogen species, while the cathodic reduction treatment can convert graphitic nitrogen and nitrogen oxides into pyridine nitrogen and pyrrole nitrogen; and the redox environment has a severe etching effect on the carbon skeleton, leading to a significant collapse of the pore structure, while the cathodic reduction environment can effectively protect the structural integrity of the carbon skeleton.

[0090] Comparing Examples 1-4 with Comparative Example 4, it can be seen that simple impregnation cannot achieve OH- - Effective loading and stable confinement within nanopores prevent the formation of effective chemisorption sites.

[0091] Comparing Examples 2-4, it can be seen that the applied voltage and the choice of electrolyte have an impact on the performance of nitrogen-doped porous carbon materials during electrochemical treatment.

[0092] Experimental Example 2 X-ray photoelectron spectroscopy (XPS) was used to perform high-resolution N 1s spectral analysis on the NPCS powder (carbon material) of Comparative Example 2 and the nitrogen-doped porous carbon powder of Example 2, respectively. The testing method is as follows: an X-ray photoelectron spectrometer was used with the AlKα line (1486.6 eV) as the excitation source. The full-spectrum scan pass energy was 200 eV, and the high-resolution fine spectral scan pass energy was 50 eV. Charge correction was performed using the C1s peak (284.8 eV) as a reference.

[0093] The results showed that pyridine nitrogen accounted for 24.4% of the total nitrogen content in the NPCS powder (carbon material) of Comparative Example 2. After cathodic electrochemical reduction functionalization, the proportion of pyridine nitrogen in the nitrogen-doped porous carbon powder of Example 2 increased to 39.8%, while the proportions of graphitic nitrogen and nitrogen oxides decreased accordingly. This data directly confirms the effective reconstruction of the chemical speciation of nitrogen species by cathodic electrochemical treatment, that is, the conversion of some chemically inert graphitic nitrogen and nitrogen oxides into more chemically active pyridine nitrogen, providing more favorable sites for the chemical adsorption of CO2.

[0094] Experimental Example 3 The nitrogen-doped porous carbon materials and powders from Examples 1 and 2 were subjected to high-speed operation elasticity tests. The test methods are as follows: The nitrogen-doped porous carbon material of Example 1 and the nitrogen-doped porous carbon powder of Example 2 were respectively packed into stainless steel adsorption columns with an inner diameter of 8 mm and a length of 150 mm. Simulated flue gas (CO2 / N2=15:85, v / v) was introduced at different flow rates of 10, 20, 40, 60 and 80 mL / min at 313 K, and the dynamic adsorption capacity at each flow rate was recorded.

[0095] The results are as follows Figure 1 As shown.

[0096] Depend on Figure 1 It can be seen that the nitrogen-doped porous carbon material of Example 1 maintains a better adsorption capacity than the nitrogen-doped porous carbon powder of Example 2 under different gas flow rates, and the advantage is more significant at higher gas flow rates.

[0097] Experiment Example 4 The nitrogen-doped porous carbon powder from Example 2, which underwent dynamic CO2 adsorption capacity testing, was desorbed at 120°C under N2 purging at a flow rate of 50 mL / min for 30 min. The CO2 desorption efficiency reached over 99%.

[0098] The nitrogen-doped porous carbon material from Example 1, after undergoing dynamic CO2 adsorption capacity testing, was directly connected at both ends to the output terminals of an electrochemical workstation (BioLogic SP-150) via copper clips. Under a nitrogen atmosphere, a constant DC voltage of 8V was applied using a potentiostat for 3 minutes. The surface temperature of the nitrogen-doped porous carbon material was monitored using a surface thermocouple. The results showed that the temperature of the nitrogen-doped porous carbon material rose from 25°C to 120°C within 1 minute of energization. After continuing energization for another 2 minutes, the power was cut off, and the material was allowed to cool naturally to room temperature. Testing showed that the adsorption capacity of the nitrogen-doped porous carbon material was completely recovered, indicating that this monolithic material possesses excellent in-situ electrothermal regeneration capabilities.

[0099] Figure 2 This is a DSC curve of the nitrogen-doped porous carbon material of Example 1 of this application, from... Figure 2 The specific heat capacity of the nitrogen-doped porous carbon material in Example 1 is 0.54 kJ / (kg·K).

[0100] The CO2 isomass adsorption heat of the nitrogen-doped porous carbon material in Example 1 was tested using the following method: A BSD-PM2 high-precision gas adsorption analyzer was used to collect CO2 adsorption isotherms of the samples at three temperatures: 303 K, 313 K, and 323 K. Before testing, the samples were degassed under vacuum at 393 K for 6 h to remove adsorbed impurities and moisture from the pores. Based on the adsorption isotherms at different temperatures, equilibrium pressures corresponding to the same adsorption amount were selected, and a plot of ln P against 1 / T was performed. Linear fitting was then performed according to the Clausius-Clapeyron equation (ln P = -Qst / (RT) + C, where P is the equilibrium pressure, Qst is the isomass adsorption heat, R is the universal gas constant, T is the thermodynamic temperature, and C is a constant). The CO2 isomass adsorption heat was calculated from the slope. The result was 69.27 kJ / mol. The isomass adsorption heat of the nitrogen-doped porous carbon material in Example 1 falls within the range of 60–80 kJ / mol, indicating that it possesses both chemisorption affinity and low-temperature regeneration characteristics.

[0101] The theoretical regeneration energy consumption of the nitrogen-doped porous carbon material in Example 1 was calculated using the following method: The theoretical regeneration energy consumption consists of two parts: the sensible heat required to heat the adsorbent from the adsorption temperature to the desorption temperature, and the desorption enthalpy that must be overcome during the CO2 desorption process. Since the adsorption capacity test uses dry CO2 / N2 simulated flue gas for the adsorption experiment, there is almost no co-adsorbed water; therefore, the latent heat of vaporization is zero. The calculation formula is as follows:

[0102] In the formula: Qr Theoretical regenerative energy consumption; C p,s Specific heat capacity of nitrogen-doped porous carbon materials; T de Desorption temperature; T ad Adsorption temperature; q CO2 mass adsorption capacity of the material; ΔHr The enthalpy of CO2 desorption is obtained by converting it from the equivalent heat of adsorption. ΔHr = Qst / M CO2 ; Qst: Heat of adsorption of CO2 at equal amounts; M CO2 : The molar mass of CO2.

[0103] The theoretical regeneration energy consumption of the nitrogen-doped porous carbon material in Example 1 was calculated to be 1.78 MJ / kg CO2, which is significantly lower than the 3.0 to 4.2 MJ / kg CO2 of the traditional alkanolamine method.

[0104] Experimental Example 5 After 10 consecutive CO2 adsorption-desorption cycles, the nitrogen-doped porous carbon powder of Example 2 showed a capacity decay rate of 24.34%.

[0105] After 10 consecutive CO2 adsorption-desorption cycles, the nitrogen-doped porous carbon material of Example 1 showed a capacity decay rate of 3.07%.

[0106] The specific methods and conditions for the CO2 adsorption-desorption cycle are as follows: Adsorption stage: The sample was packed into a stainless steel adsorption column with an inner diameter of 8 mm and a length of 150 mm. Before the test, the column was purged with high-purity N2 at a flow rate of 30 mL / min at 393 K for 6 h to degas in situ, and then cooled to 313 K. Simulated flue gas with a volume ratio of 15:85 CO2 / N2 was introduced at a flow rate of 50 mL / min. The outlet CO2 concentration was monitored in real time using an online CO2 analyzer. When the outlet CO2 concentration reached 95% of the inlet concentration, adsorption breakthrough was determined, and the adsorption capacity of this cycle was recorded.

[0107] Desorption stage (for nitrogen-doped porous carbon powder in Example 2): The adsorption column temperature was kept at 120°C, and high-purity N2 was introduced at a flow rate of 50 mL / min for 30 min to complete CO2 desorption; after desorption, the column was cooled to 313 K and the next adsorption-desorption cycle began.

[0108] Desorption stage (for the monolithic nitrogen-doped porous carbon material of Example 1): The two ends of the sample are connected to the output terminals of an electrochemical workstation (BioLogic SP-150) via copper clips. Under N2 atmosphere protection, a constant DC voltage of 8 V is applied for 3 min, and the sample self-heats to 120°C to complete CO2 desorption; then the power is cut off and the sample is allowed to cool naturally to 313 K to enter the next round of adsorption-desorption.

[0109] Repeat the above adsorption-desorption steps and conduct 10 consecutive cycles of testing.

[0110] The capacity decay rate is calculated using the following formula: Capacity decay rate (%) = (First adsorption capacity - Tenth adsorption capacity) / First adsorption capacity × 100%.

[0111] This invention is not limited to the above-described embodiments. Any modifications, improvements, or substitutions that can be conceived by those skilled in the art without departing from the essential content of this invention fall within the scope of this invention.

Claims

1. A method for preparing nitrogen-doped porous carbon material, characterized in that, Includes the following steps: (1) The nickel foam was immersed in a precursor solution containing carbon and nitrogen sources for hydrothermal reaction to obtain supported nickel foam; the supported nickel foam was carbonized to obtain NPCS@NF; (2) Using NPCS@NF as the working electrode, electrochemical treatment was carried out in a three-electrode system to obtain nitrogen-doped porous carbon material; wherein, the working electrode is the cathode and the electrolyte is an aqueous solution of nitrate.

2. The preparation method according to claim 1, characterized in that, In step (2), the counter electrode is platinum and the reference electrode is Ag / AgCl; a negative potential of -0.5 to -2.5V is applied to the working electrode.

3. The preparation method according to claim 1, characterized in that, In step (1), the carbon source is selected from one or more of glucose, sucrose, and cellulose, and the nitrogen source is selected from one or more of urea, ethylenediamine, triethylamine, and acrylamide; the mass ratio of the carbon source to the nitrogen source is (3-6):(1-3); In step (2), the nitrate in the nitrate aqueous solution is selected from one or more of potassium nitrate, sodium nitrate, and lithium nitrate, and the concentration of the nitrate aqueous solution is 0.1 to 0.9 mol / L.

4. The preparation method according to claim 1, characterized in that, The precursor solution also includes a zinc carboxylate salt, which is selected from one or more of zinc formate, zinc acetate, and zinc propionate, and the mass ratio of the carbon source to the zinc carboxylate salt is (3-6):(0.05-0.5).

5. The preparation method according to claim 1, characterized in that, The precursor solution also includes water and an aliphatic alcohol with 1 to 6 carbon atoms, with a volume ratio of water to aliphatic alcohol of 85:(5 to 25).

6. The preparation method according to claim 1, characterized in that, The hydrothermal reaction was carried out at a temperature of 390–450 K for 5–10 h. Carbonization is carried out under a nitrogen atmosphere at a temperature of 650–850 K for a time of 0.5–3 h.

7. A method for preparing nitrogen-doped porous carbon powder, characterized in that, Includes the following steps: (1) The nickel foam was immersed in a precursor solution containing carbon and nitrogen sources for hydrothermal reaction to obtain supported nickel foam; the supported nickel foam was carbonized to obtain NPCS@NF; (2) Using NPCS@NF as the working electrode, electrochemical treatment was carried out in a three-electrode system to obtain nitrogen-doped porous carbon material; wherein, the working electrode is the cathode and the electrolyte is an aqueous nitrate solution; (3) Separate the powder attached to the surface of the nitrogen-doped porous carbon material from the matrix nickel foam to obtain nitrogen-doped porous carbon powder.

8. A nitrogen-doped porous carbon material, characterized in that, The nitrogen-doped porous carbon material is obtained by the preparation method according to any one of claims 1 to 6.

9. A nitrogen-doped porous carbon powder, characterized in that, The nitrogen-doped porous carbon powder is obtained by the preparation method described in claim 7.

10. The use of the nitrogen-doped porous carbon material according to claim 8 or the nitrogen-doped porous carbon powder according to claim 9 in the adsorption of CO2 gas.

Citation Information

Patent Citations

  • Electricity-loaded adsorbent for direct air trapping as well as preparation method and application of electricity-loaded adsorbent

    CN121669170A